Comparison between logbook-reported and objectively-assessed physical activity and sedentary time in breast cancer patients: an agreement study - Anne-Sophie Mazzoni; Karin Nordin; Sveinung Berntsen; Ingrid Demmelmaier; Helena Igelström (BMC, 2017)
Abstract Background Increasing physical activity (PA) and decreasing sedentary time (ST) have important health effects among breast cancer patients, a growing population group. PA and sedentary behaviors are complex multi-dimensional behaviors and are challenging to monitor accurately. To date few studies have compared self-reports and objective measurement in assessing PA and ST in women undergoing breast cancer treatments. The aim of the present study was to compare self-reports and objective measures for assessing daily time spent in moderate-intensity physical activity (MPA), vigorous-intensity physical activity (VPA) and ST in women undergoing breast cancer treatments. Methods Baseline data from 65 women with breast cancer scheduled to undergo adjuvant treatment was included. Daily time spent in MPA, VPA and ST was assessed by a study-specific logbook and the SenseWear Armband mini (SWA). The level of agreement between the two measurement methods was then determined by performing Bland-Altman plots with limits of agreements, and calculating Spearman's rank correlation coefficients. Results The mean difference between the logbook and SWA with limits of agreement was 14 (±102) minutes for MPA, 1 (±21) minute for VPA and −196 (±408) minutes for ST, respectively. The logbook reported an average of 34 and 50% higher values than the SWA for MPA and VPA, as well as an average of 27% lower values for ST (P < 0.05). The Spearman's rank correlation coefficients showed that the differences between the methods increased as the average amount of time spent in PA and ST increased (P < 0.01). Conclusions The results imply that the two measurement methods have limited agreement and cannot be used interchangeably.